The Influence of Promotion, Online Customer Reviews, and Price on Generation Z’s Purchase Decisions at Belia Cosmetic in the Shopee Marketplace (Study on Consumers in Surabaya) - R. Yuniardi Rusdianto; Ra Nadia Triyana Serli (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to determine and analyze the influence of promotion, online customer reviews, and price on the purchasing decisions of Generation Z at Belia Cosmetic on the Shopee marketplace (a study of consumers in Surabaya). The research is motivated by the increasing competition in the cosmetics and skincare industry within marketplaces and the changing behavior of Generation Z, who are becoming more selective in considering promotions, customer reviews, and prices before making purchasing decisions. This study employed a quantitative method with an associative approach. The population consisted of Generation Z consumers who had purchased Belia Cosmetic products through Shopee, and the sample was selected using simple random sampling with a total of 100 respondents who met the research criteria. Data were collected through questionnaires using a Likert scale and analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, the coefficient of determination (R²), and hypothesis testing through t-tests and F-tests. The results indicate that promotion, online customer reviews, and price simultaneously have a significant effect on purchasing decisions. Partially, promotion has a positive and significant effect on purchasing decisions, online customer reviews have a positive and significant effect on purchasing decisions, and price has a positive and significant effect on purchasing decisions. Among the variables, online customer reviews have the most dominant influence on Generation Z purchasing decisions at Belia Cosmetic on the Shopee marketplace. This study is expected to serve as a reference for companies in optimizing marketing strategies, particularly in managing customer reviews to enhance purchasing decisions among Generation Z consumers. Keywords: Promotion, Online Customer Review, Price, Purchasing Decision, Generation Z.